Francophone African Literary Prizes and the "Empire of the French Language" - (:unkn) unknown (My University, 2015)
Discussions surrounding the Caine Prize for African Writing and the Nobel committee’s apparent neglect of Africa both defend and challenge the role of prizes in a global literary marketplace. While encouraging new writing in the continent and among its diaspora, the steep growth in literary prizes in the latter half of the twentieth century is bound up with the increased commercialisation and mediatisation of art. Prize culture can reinforce normative ideas of literary value, innovation and creative expression in response to pressure from politics and commerce. This chapter will consider the colonial heritage of the main literary prize specific to African writing in French: the Grand prix littéraire de l’Afrique noire, awarded by the Association des écrivains de langue française (ADELF). The history of this association, active from 1924 to the present day under several different names, is that of contact and exchange between writers who might be assumed to occupy very different areas of colonial and postcolonial literary space. As we will argue, in the French-language context, the longer-term history of prize culture for African literature illustrates significant structures of recognition and reception in the literary field. These structures reveal the ambivalent role of this prize — and of metropolitan literary judgement more broadly — in the construction of France’s postcolonial cultural narratives.
Keywords: African Research